Production Factor Mathematics - Grötschel, Martin; Lucas, Klaus; Mehrmann, Volker (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Mathematics as a production factor or driving force for innovation? Those, who want to know and understand why mathematics is deeply involved in the design of products, the layout of production processes and supply chains will find this book an indispensable and rich source. Describing the interplay between mathematical and engineering sciences the book focusses on questions like - How can mathematics improve to the improvement of technological processes and products - What is happening already? - Where are the deficits? - What can we expect for the future? 19 articles written by mixed teams of authors of engineering, industry and mathematics offer a fascinating insight of the interaction between mathematics and engineering.